Odpowiedzi

2010-01-24T14:35:49+01:00
(5x-4y)^2-(x-4y)(x+4y)-6(3x-6y)^2 = 10x - 8y + x² + 4y² (- 18x + 36y) *2 = 10x - 8y + x² + 4y² - 36x + 72 y
2010-01-24T14:35:59+01:00
(5x-4y)^2-(x-4y)(x+4y)-6(3x-6y)^2 = 25x^2 - 40xy + 16y^2 -(x^2 + 4xy - 4xy - 16y^2 - 6(9x^2 - 36xy + 36y^2) = 25x^2 - 40xy + 16y^2 - x^2 + 16y^2 - 54x^2 +216xy - 216 y^2 = -30x^2 - 184y^2 + 176xy
2010-01-24T14:42:54+01:00
(5x-4y)^2-(x-4y)(x+4y)-6(3x-6y)^2 = 25x^2-40xy-x^2+16y^2 - 6(9x^2 - 36xy + 36y^2) = 25x^2 - 40xy - x^2 + 16y^2 - 54x^2 +216xy - 216 y^2 = -30x^2 - 200y^2 + 176xy